Economic valuation of wildlife-based ecotourism resources in Yankari Game Reserve, Bauchi State Nigeria - Adamu, Abdullahi (2015)
Natural resources in general and biodiversity in particular provide numerous functions that includes; hydrological such as the hydrological cycle and soil formation, ecological, including; nitrogen fixation and carbon sequestration, social, and economic such as the ecotourism opportunity, research and education benefits to the society. However, the absence of market for these resources negatively affects the way and manner by which they are being treated by the society which subsequently reduced the numerous benefits that are derived from them. The economic valuation of these non-marketed goods helps to find and attach price or economic values to them. Therefore, as these environmental resources are usually not traded in the market, the non-market valuation techniques are applied to estimate their economic value common among them is the Contingent Valuation Method (CVM) which have been widely used to measure the economic value of natural resources. The main purpose of this study is to estimate the use and non-use values of wildlife-based ecotourism resources in Yankari game reserve using environmental economic tools. The study employed the Dichotomous choice Contingent Valuation Method (DC-CVM) on 335 on-site local visitors to estimate the use value of the ecotourism resources in Yankari and 237 local residents from the adjacent communities to the reserve to investigate the non-use value. Logit regression model was used in estimating the use and non-use values of the resources. The result revealed that gender, age, education level, gross monthly income, bids amount and visit frequency were significant determinants of the willingness to pay by the Visitors for an increase in the entrance fee into the game reserve. On the other hand the respondents‘ age, gross monthly income, bid amount and attitudes towards the environment resources were important determinants of willingness to pay by the non-users to pay a donation for conservation of resources in Yankari. The result also showed that the visitors are willing to pay N 508 (US$ 3.4) for conservation as against the current entrance fee of N 300 (US$ 1.8) and the use value of the reserve was estimated to be N 960,468.5 (US$ 6002.93) based on average annual visitors to the reserve. The non-users mean willingness to pay was calculated at N 594 (US$ 3.71) and the non-use value was also estimated at N 32,500,116 (US$ 203,125.73). Therefore, the total benefit of conservation of the reserve is approximately N 33,460, 584.5 million (US $ 209,128.65). Results of this study would help to assist policy makers and the management of the reserve especially in terms of revenue generation. This information can be used to estimate the benefits for further investment in the reserve, to value the game reserve according to demand if there are budget deficit, and in particular to invest for biodiversity conservation.